Multiple isolated ovarian cancer recurrences in the cervix and vagina after supracervical hysterectomy: A case report - Anh Q. Nguyen; Sarah Ehmann; Jaqueline Feinberg; William P. Tew; Karen Carthew; Yuko Sonoda; Dennis S. Chi (Elsevier, 2022)
We present a rare case of a patient who was treated for advanced-stage ovarian cancer with optimal debulking surgery that included a supracervical hysterectomy, instead of total abdominal hysterectomy, who subsequently developed 3 isolated recurrences in the cervix and vagina. We suggest there may be a link between the type of hysterectomy and location of recurrence; we also emphasize the importance of pelvic exam and Papanicolaou smear for patients who have undergone supracervical hysterectomy as part of their ovarian cancer debulking surgery.